27-GAUGE NEEDLE-ASSISTED TECHNIQUE FOR REPOSITIONING A DISLOCATED INTRAOCULAR LENS. Issue 9 (September 2016) - Li, Pei-Hsuan; Tseng, Gow-Lieng; Wu, Shao-Chi; Liou, Shiow-Wen
Abstract : Background: Several techniques for the reposition of a posterior chamber intraocular lens (IOL) posterior dislocating into the vitreous cavity have been developed. However, most of these methods are complicated or include externalizing part of the IOL from a corneal or scleral wound. We here describe a 27-gauge needle-assisted technique for management of a dislocated posterior chamber IOL. Methods: This is a retrospective, noncomparative, interventional case series that discusses the results of 27-gauge needle-assisted reposition of the posterior chamber IOL with transscleral sulcus fixation in 5 consecutive cases with an IOL dislocated into vitreous cavity. These patients underwent IOL reposition with the above-mentioned technique between April 2013 and October 2014 and were followed up for at least two months thereafter. Results: The IOLs of the five cases were stable with proper centrations. The postoperative best-corrected visual acuity ranged from 20/30 to 20/20. Conclusion: The technique of 27-gauge needle-assisted reposition of the posterior chamber IOL with transscleral fixation is effective for reposition of a dislocated IOL. This technique provides good IOL fixation without creating a large corneal wound or scleral flap. Abstract : Supplemental Digital Content is Available in the Text.Several techniques for repositioning a dislocated posterior chamber intraocular lens (IOL) have been developed. In our preliminary study, we describe a 27-gauge needle-assisted technique for repositioning the posterior chamber IOL. This technique provides IOL fixation through few sclerotomies—23-gauge sclerotomies for standard sutureless 3-port pars plana vitrectomy and 27-gauge sclerotomies for delivering the sutures.